Analytical solutions for bending, buckling and vibration analysis of functionally graded cylindrical panel - Huan, Duong Thanh; Tu, Tran Minh; Quoc, Tran Huu (Vietnam Journal of Science and Technology, 2017)
The main purpose of this article is to present analytical solutions for bending, buckling and vibration analysis of cylindrical panel, which are composed of functionally graded materials (FGMs). Equations of motion are derived using Hamilton’s principle. The first-order shear deformation theory is used for developing Navier’s solutions of simply supported cylindrical panel. Comparison studies are presented to verify the validity of present solution. It is found that the presented results are close to those existing. The effect of volume fraction distributions, panel aspect ratio, and side-to-thickness ratio on the deflections, buckling loads and natural frequencies is also investigated.